1990
DOI: 10.1164/ajrccm/141.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Polymyositis and Dermatomyositis: Clinical Features and Prognosis as Correlated with Histologie Findings

Abstract: Open lung biopsies from 14 patients and autopsy tissue from one patient with polymyositis/dermatomyositis were reviewed in an attempt to correlate histologic features with clinical, radiographic, and prognostic variables. Three major groups based on histologic patterns were identified: bronchiolitis obliterans organizing pneumonia (BOOP), usual interstitial pneumonia (UIP), and diffuse alveolar damage (DAD). Patients with BOOP had a more favorable prognosis than did patients with UIP. Patients with DAD had a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
198
0
11

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(213 citation statements)
references
References 16 publications
4
198
0
11
Order By: Relevance
“…Several studies on the histopathology of ILD-PM/DM have demonstrated various histological patterns, such as UIP, NSIP, BOOP and DAD, and emphasised their prognostic significance [13,[25][26][27]. However, limited data are available on the histopathology of ILD-ADM. LEE et al [7] recently reported three cases of acute ILD-ADM with a histological finding of DAD, which was associated with poor outcome; whilst COTTIN et al [13] described three patients with chronic ILD-ADM who showed NSIP with a good prognosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the histopathology of ILD-PM/DM have demonstrated various histological patterns, such as UIP, NSIP, BOOP and DAD, and emphasised their prognostic significance [13,[25][26][27]. However, limited data are available on the histopathology of ILD-ADM. LEE et al [7] recently reported three cases of acute ILD-ADM with a histological finding of DAD, which was associated with poor outcome; whilst COTTIN et al [13] described three patients with chronic ILD-ADM who showed NSIP with a good prognosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BOOP generally have a more favorable prognosis compared to those with diffuse alveolar lesions or interstitial pneumonia. 25,26 In our patients, there was one patient with clinical findings consistent with BOOP who had a good outcome after corticosteroid therapy. The presence of pulmonary hypertension is reported in the literature and is associated to interstitial pulmonary disease.…”
Section: Discussionmentioning
confidence: 66%
“…Three major groups can be identified: bronchiolitis obliterans with organizing pneumonia (BOOP), usual or nonspecific interstitial pneumonia, and diffuse alveolar damage. The histologic appearance of interstitial lung disease in patients with polymyozitis and dermatomyozitis is a prognostic factor (13). Diffuse alveolar damage and usual interstitial pneumonia are poor prognostic subtypes, with only a 33% 5-years survival rate (13).…”
Section: Discussionmentioning
confidence: 99%
“…The histologic appearance of interstitial lung disease in patients with polymyozitis and dermatomyozitis is a prognostic factor (13). Diffuse alveolar damage and usual interstitial pneumonia are poor prognostic subtypes, with only a 33% 5-years survival rate (13). However, BOOP and nonspecific interstitial pneumonia have better prognosis.…”
Section: Discussionmentioning
confidence: 99%